Implementation of Integrated Virtual Counseling in a Laravel-Based E-Learning System - Nawang Rimarsha Alifdyani; Joko Iskandar; Yayak Kartika Sari (Jurnal Teknologi Informatika dan Komputer, 2026)
The use of digital technology is one way to improve effectiveness, efficiency, and broaden service reach. One example of this technology is e-learning, which allows for flexible learning without the constraints of time and space. The development of information technology is not only having a national impact but is also a global phenomenon, driving digital transformation across various sectors, including education. The development of information technology encourages government institutions to transform educational and counseling services into digital platforms. BNN Kabupaten Tulungagung requires a system capable of integrating online learning with counseling services within a single integrated platform. This study aims to implement virtual counseling in a Laravel-based e-learning system using the Prototype method and to conduct functional testing using Black Box Testing. The Prototype method was applied through several stages including requirement communication, system design, prototype development, and iterative evaluation. The system developed includes pretest, learning materials, posttest, digital certificates with QR Code, an admin dashboard, and virtual counseling features that allow users to conduct online consultations with BNN officers, as well as an FAQ feature for additional information. The testing results indicate that the system functions according to the required specifications and can be used effectively by both users and administrators. The implementation of this system supports the digital implementation of the P4GN education program and provides a more accessible counseling service for the community at BNN Kabupaten Tulungagung.